2002
DOI: 10.1021/la011273q
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Temperature on Surfactant-Driven Water Movement in Wet “Unsaturated” Sand

Abstract: The effect of temperature on the surfactant-driven movement of water in wet “unsaturated” sand was investigated and correlated with the equilibrium spreading pressure of the surfactant and the character of the surfactant monolayer at πe. The previously determined criteria for surfactant effectiveness were confirmed. An approximately linear relationship between πe and the amount of water moved by effective surfactants was found. Temperature changes affect water movement by influencing the surfactant πe and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
4
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 6 publications
2
4
0
Order By: Relevance
“…Figure qualitatively demonstrates that both myristyl alcohol and butanol can move significant quantities of water, though the two systems exhibit distinct differences. The general behavior observed in the myristyl alcohol experiments (Figure a) is very similar to that reported by Karkare and colleagues ,,, for the same surfactant. Surfactant-induced capillary pressure gradients between the LHS and RHS of the column caused water to drain from the RHS and resulted in wetting of the LHS.…”
supporting
confidence: 88%
See 2 more Smart Citations
“…Figure qualitatively demonstrates that both myristyl alcohol and butanol can move significant quantities of water, though the two systems exhibit distinct differences. The general behavior observed in the myristyl alcohol experiments (Figure a) is very similar to that reported by Karkare and colleagues ,,, for the same surfactant. Surfactant-induced capillary pressure gradients between the LHS and RHS of the column caused water to drain from the RHS and resulted in wetting of the LHS.…”
supporting
confidence: 88%
“…We have followed with great interest the work of Karkare, Fort, and colleagues related to the ability of surfactants to move water in unsaturated porous media. In their most recent work, Karkare and Fort extend their previous work to include the effect of temperature. They report that the results of the present study support the conclusions of their previous work.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Karkare et al (1993) applied the closed horizontal column technique to study the ability of 33 surfactants to move water and found that, in order for surfactants to be effective at moving water, “they must be water‐insoluble and must form a condensed solid film at their equilibrium spreading pressure.” Tschapek et al (1984) and Karkare and Fort (2002) reached a similar conclusion. However, Henry et al (1999) showed that surfactant‐induced capillary pressure gradients caused by a high‐solubility alcohol, 1‐butanol, were sufficient to produce effective water movement in the closed soil columns.…”
Section: Experimental Studies Of Surfactant‐induced Flowsupporting
confidence: 63%
“…For example, nonuniform surfactant distributions have been shown to cause water to flow in unsaturated, uniformly wetted, closed, horizontal soil columns that would have remained static without surfactants. The observed flow was directly due to capillary pressure gradients caused by concentration‐dependent surface tension differences (e.g., Tschapek and Boggio, 1981; Karkare and Fort, 1993, 2002; Henry et al, 1999, 2001; Henry and Smith 2002; Bashir et al, 2008, 2009).…”
mentioning
confidence: 99%